Highly-Ordered Growth of Solution-Processable ZnO for Thin Film Transistors. (25th April 2017) - Buckley, Darragh; McNulty, David; Zubialevich, V.Z.; Parbrook, Peter J.; O'Dwyer, Colm
Abstract : We demonstrate that crystalline, epitaxial-like and highly ordered ZnO thin films and quasi-superlattice structures can be achieved from a precursor liquid at relatively low temperature via spin-coating. The synthesised films are smooth, stoichiometric ZnO with controllable thickness. An iterative layer-by-layer coating schematic is employed to demonstrate the effects of film thickness on structure, morphology as well as the surface and internal defects. Characterisation of the crystallinity, morphology, O-vacancy formation, stoichiometry, surface roughness and thickness variation was determined through X-ray diffraction, scanning and transmission electron and atomic force microscopy, X-ray photoelectron and photoluminescence spectroscopy. We demonstrate that iterative spin-coating of deposited ZnO films results in a transition in crystal texture with increasing thickness (number of layers) from the [ ] m-plane to the [ ] c-plane. The films attain a c-axis preferential orientation, with no other crystalline peaks present. Results show that the film's surface morphology was very smooth, with average rms roughness <0.15 nm. Examination of these films also shows the consistency of the surface composition and defect level while highlighting the effect of temperature and cumulative annealing condition on the internal defect concentration.